Perbandingan Tingkat Kenyamanan Pasca Pembiusan Umum dengan LMA Classic dan LMA Proseal di RSUD Arifin Achmad Provinsi Riau - Dino Irawan; Nopian Hidayat (Fakultas Kedokteran Universitas Riau, 2024)
Airway management during general anesthesia can be done using a triple airway maneuver or the installation of devices such as a face mask, laryngeal mask airway (LMA), and endotracheal tube/ETT. There are various types of LMA, namely classic, proseal, supreme, and various other types. Throat pain is the most common intubation complication experienced by patients after anesthesia. The incidence of throat pain can be influenced by several things, one of which is the choice of type of LMA used. This study uses an experimental design and is a randomized controlled trial. In September and October of 2019, this study was carried out at the Arifin Achmad Hospital in the Province of Riau. Patients who received LMA intubation along with general anesthesia in September and October 2019 at Arifin Ahmad Hospital comprised the research population. The findings indicated that throat pain was more common in 14 individuals (17.5%) treated with LMA Classic than in 12 patients (15%) treated with LMA Proseal. The age groups 46–55 and 55–65 have the highest incidence of throat pain, which is also more common in women, patients with a history of smoking, and patients who have been intubated for longer than an hour.